If you mean: y = -4x+12 then the slope is -4 and the y intercept is 12
Chat with our AI personalities
2y - 4x = -12 Algebraically rearrange to 2y = 4x - 12 Divide both sides by '2' y = 2x - 6 So at the 'y' intercept, x = 0 Substituting x = 0 We have y = 2(0) - 6 Anything multiplied '0' is equal; to '0' Hence y = 0 - 6 y = -6 is the value of the y-intercept.
If you mean: 2y = -4x-12 then y = -2x-6 and -6 is the y intercept
4x+3y = 12 3y = -4x+12 y = -4/3x+4
(4x)(2y) would be factored as such: 4x = 2 • 2 • x 2y = 2 • y 2(2x)(y)
It shows the relationship of y in terms of x. [y = (yIntercept) + ((slope)*(x))] [slope = (y2 - y1)/(x2 - x1)]